Pemrograman Sudut-Sudut Kinematis pada Persendian Kaki Robot untuk Menstabilkan Gerak Maju Robot Quadruped - Akhmad Rizal Dzikrillah; Gripsy Adeep Firmansyah; Abrar Dhiya Rabbani; Yoga Budi Santoso; Malik Emir Hafta; Rosalina; Fadhlan Nurrachman (Prosiding Seminar Nasional Teknoka, 2023)
In the 2023 Indonesian SAR robot contest, intelligent robots from each university compete to score by carrying orange mini dolls to designated locations. Robots must overcome various difficult obstacles. The intelligent robot in the competition is a legged robot that has clamps for holding mini dolls. Servo motors are one of the motors that are often used in legged robot joints. This research aims to program the kinematic angles of the joints of a legged robot so that it is able to traverse the 2023 SAR Robot Contest arena and its obstacles stably. By using 4 legs, namely front-right, front-left, rear-right and rear-left and using 3 servo motors on each leg, the robot can walk stably after programming certain kinematic angles on the servo motor. The robot is programmed to have 7 phases of movement between the legs that are aligned with a delay of 500 milliseconds for each phase. The robot can walk stably over all obstacles in the KRSRI 2023 robot arena except for the uphill stairs.